Time Orientation and Its Relationship to Well-Being Among University Youth in The City of Erbil - Saber Muhammad Othman; Maha Hassan Baker (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
The construction of the concept of time is generated from cognitive processes, it is one of the essential dimensions in the psychology of time, through (Time Orientation), and a person describes his experiences in temporal cognitive frameworks or patterns (past - present - future. These patterns have an impact on the decisions a person makes and the behaviors he performs. The researcher used the following scale to collect data: Adoption of the scale which developed by (Zimbardo et Boyd, 1999) for time orientation. And the results were as follows: High level of time orientations and among the research sample. There are no significant differences between the means of the responses of the research members on the dimensions of time orientations (past, present and future) according to the specialization variable. There are no statistically significant differences between males and females in the dimensions of the time perspectives. The level of time orientations according to the stage variable, the results indicated that the percentage of temporal orientations toward the past among research sample is statistically significant.